Evaluation of the school-based ‘PhunkyFoods’ intervention: a cluster randomised controlled trial in the UK - Karen L. Vaughan; Milca Vidal; Janet E. Cade; Marion M. Hetherington; Charlotte E.L. Evans (Public Health Nutrition)
Abstract